Next Generation intraoperative Lymph node staging for Stratified colon cancer surgery (GLiSten) : a multicentre, multinational feasibility study of fluorescence in predicting lymph node-positive disease /: a multicentre, multinational feasibility study of fluorescence in predicting lymph node-positive disease. (August 2016) - (Clinical Research Fellow), Andrew, Helen
No abstract available